Sistem Pakar Diagnosa Kerusakan Pada Vespa Matic Menggunakan Metode Naïve Bayes Berbasis Web (Studi kasus : PT. Dwi Pratama Mandiri) - Faisal, Ahmad; Heri Yunial, Agus (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
The automotive industry in Indonesia is experiencing rapid growth in line with the increasing public need for transportation. Vespa, as a scooter motorcycle brand from Piaggio, an Italian company, contributes to Indonesia's automotive economy. PT Dwi Pratama Mandiri is an authorized dealer of Vespa Matic. Observations show that most consumers still do not understand the potential damage to their vehicles. Expert systems, a branch of artificial intelligence, can be a solution to increase consumer knowledge and speed up the process of identifying defects. The Naïve Bayes method, a probabilistic classification algorithm, has proven efficient in the analysis of complex problems. Previous research shows that this method has a high accuracy rate of up to 96%.. This research aims to help consumers detect and overcome problems with their vehicles, and can improve consumer understanding of damage to Vespa Matic.